Transcriptomics and Metabolomics Reveal Purine and Phenylpropanoid Metabolism Response to Drought Stress in Dendrobium sinense, an Endemic Orchid Species in Hainan Island - Zhang, Cuili; Chen, Jinhui; Huang, Weixia; Song, Xiqiang; Niu, Jun (Frontiers in Genetics, 2021)
Drought stress is a bottleneck factor for plant growth and development, especially in epiphytic orchids that absorb moisture mainly from the air. Recent studies have suggested there are complex transcriptional regulatory networks related to drought stress in Dendrobium sinense. In this study, the transcription and metabolite alterations involved in drought stress response in D. sinense were investigated through RNAseq and metabolomics. A total of 856 metabolites were identified from stressed and control samples, with 391 metabolites showing significant differences. With PacBio and Illumina RNA sequencing, 72,969 genes were obtained with a mean length of 2486 bp, and 622 differentially expressed genes (DEGs) were identified. Correlation analysis showed 7 differential genes and 39 differential metabolites were involved in interaction networks. The network analysis of differential genes and metabolites suggested that the pathways of purine metabolism and phenylpropanoid biosynthesis may play an important role in drought response in D. sinense. These results provide new insights and reference data for culturally important medicinal plants and the protection of endangered orchids.